Mount St. Helens - Green, Jen. frey50 (Milwaukee : Gareth Stevens Pub., 2005)
Describes the events prior, during, and after the erruption of Mount St. Helens.
Keywords: Volcanoes -- Washington (State); Volcanoes -- Washington (State); Saint Helens, Mount (Wash.) -- Eruption, 1980; Saint Helens, Mount (Wash.) -- Eruption, 1980.